Adaptive reuse of old colonial building, Muar as gallery & resource centre design: a comparative study on Islamic architecture influence towards Kuala Lumpur colonial buildings - Nur Amalina Hanapi,; Leng, Pau Chung (Penerbit Universiti Kebangsaan Malaysia, 2022)
While several studies have noted on the effectiveness of reusing historical colonial buildings as sustainable mechanism, there is still an absence of Islamic influence study on the performance-based framework to rank optimal usage element in historical building as resource centre and gallery. This research focusses on the elements of Islamic influence in old colonial building to be imparted as part of the framework study for an adaptive reuse library and gallery. The methodology comprises of case studies on identifying current Islamic layout influence demarcation of the old colonial building and at the same time evaluating possible elements for adaptive reuse library and gallery towards achieving resilient building. With the invited collaboration of library design study from Muar, Johor parliament for community library, an initiative proposal study of adaptive reuse old colonial which was previously an office building in Jalan Othman been made aligned with an approach to local authority, Majlis Perbandaran Muar with the council vision of low carbon city for the town. Several case studies of colonial building will be selected to explore the Islamic principles, garden element and design development to balance their framework screening for the vacant colonial office building. The findings are anticipated to establish useful validated framework in balancing the list of priorities and interests of Islamic design principles for designing future adaptive reuse library and gallery in Muar. Hence, this research provides a significant contribution to the development of design framework will then enabling the decision makers to achieve a logical result and support the visualization impact of different priority of Islamic principal elements and criteria on colonial buildings.